The Relationship Between Hemisphere Dominant and Organizational Support Among School Principals - Salim, Maha Sabry (Journal of Educational and Psychological Sciences, 2020)
The aim of the research was to identify Organizational Support and its relation to Hemisphere Dominant among principals, The researcher used the descriptive approach and the sample of the study was (200) principals of primary school. The researcher used the Organizational Support scale for Eisenberger et al. (1986). The validity (translation, face validity, construction), McCrone’s Hemisphere Dominant scale and psychometric properties. The results of the study were used to test the results of a single sample, a square of Ka2, a cross call test, and a search for a number of results. The most important results were: the existence of a statistically significant difference in primary school principals in Organizational Support in general ; For school principals, but the results did not show statistically significant differences in school principals in Organizational Support according to Hemisphere Dominant.